Strand‐specific RNA sequencing uncovers chloroplast ribonuclease functions. Issue 18 (14th August 2013) - Castandet, Benoît; Hotto, Amber M.; Fei, Zhangjun; Stern, David B.
Abstract : Organellar gene expression incorporates ribonucleases as indispensable participants. Here, we explored the capacity of strand‐specific RNA sequencing (RNA‐Seq) as a tool to analyze chloroplast ribonuclease functions using the 3′→5′ exoribonuclease polynucleotide phosphorylase (PNPase) as a proof of concept. The role of PNPase in transcript 3′ end maturation was easily monitored, and additional targeted mRNAs were discovered. Moreover, a role in tRNA precursor degradation was predicted and validated. These results, together with previously published data, suggest that RNA‐Seq represents a unique opportunity to decipher the roles of organellar ribonucleases and deepen our understanding of chloroplast gene expression. Abstract : RNA‐Seq was used to identify targets of the chloroplast 3′→5′ exoribonuclease PNPase. Both known and new‐found roles of PNPase in 3′ end formation were easily monitored. An unknown role in tRNA precursor degradation was predicted and validated. This work points to a broad applicability of RNA‐Seq to studies of organellar RNA metabolism.